Carmen Valero-Garcés. 2014. Communicating Across Cultures: A Coursebook on Interpreting and Translating in Public Services and Institutions. - Fernández Polo, Francisco Javier (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2015)
.